Nutrient cycling in a montane moist evergreen broad-leaved forest (Lithocarpus/Castanopsis association) in Ailao Mountains, Yunnan, Southwestern China. - Liu, Wenyao (Curtin University, 2001)
This study was conducted at the Ailao Mountain National Natural Reserve (NNR) in natural vegetation described as: Lithocarpus xylocarpus/Castanopsis wattii (Oak /Chestnut association) forest. Study sites were located in the Xujiaba area of the reserve at an altitude of ~ 2450 m with slopes of 10-15 degrees. This type of forest is believed to be unique to the NEAR area. The forest is floristically characterized by multiple families and genera. It has two tall tree layers, a well-developed bamboo (Sinarundinaria nitida) layer and evergreen fern species. Bryophyte, ferns and lichen occur and abundant epiphytic bryophyte is present on tree boles.A number of important aspects of nutrient cycling, including patterns of biomass and nutrient accumulation; nutrient return in litterfall and release from decomposing leaf litter; annual nutrient uptake and retention, and nutrient input and output budgets through hydrological flux in natural Lithocarpus/Castanopsis forest in the reserve, were investigated.This natural forest is characterized by high biomass accumulation of living and dead materials. Trees account for >90 % of total biomass. Dead wood comprises a high proportion (9-41 %) of total stand biomass. The sequence of inorganic nutrient element content decreased in the order leave s>b ranche s>roots> stems. Elemental content of the total stand decreased in the order of C>Ca>N>K>AI>Mg>P>Fe>Mn. The elements C, Ca and N were mainly in stems while AI and Fe were mainly in roots.Litterfall was sampled using traps during the period 1991-1999. High variations in litter production between years were associated with masting years of canopy species, and exceptional physical events (strong winds and snow). The mean annual litterfall is 7.12 t ha-1 with a bimodal seasonal pattern in litterfall: the main litterfall peak occurred in April-May and a lesser one in October-November. Woody litter and reproductive parts contribute relatively high proportions in this natural forest compared with other montane forests. Woody litter had low N and P concentrations compared with the leaf and reproductive parts. Elements return to the soil through small litterfall decreases in the order C>N>Ca>K>Mg>Mn>AI>P>Fe.The standard litter-bag technique was used to determine decomposition of leaf litter from three dominant canopy species (L. xylocarpus, L. chintungensis, C. wattii), one dominant understory species (the bamboo S. nitida) and a mixture of dominant bryophytes between Nov. 1997 and Oct. 1999. In each case, fast initial litter decomposition was followed by lower rates. Decomposition rates of canopy species and bamboo leaf litter appear to be controlled by initial concentration of lignin, N and P more than by morphological features of the leaves. P seemed to limit decomposition of all leaf litter, both initially and later. Nutrient release from decomposing leaf litter is in the order of K>Mg>Ca>N>P>~Fe, except for bamboo (S. nitida) K>Ca> P>N>Mg>Mn>Fe.Nutrient fluxes in bulk precipitation, throughfall and stemflow were measured in the natural forest between Jan. 1998 and Dec. 1999. This forest exhibited low interception by the canopy (13 % of total rainfall). N, P, Ca and S annual throughfall inputs were mainly from precipitation, while most of the K and two thirds of the Mg throughfall input was due to canopy leaching. There were significant effects of epiphytes on the amount and chemical composition of stemflow. Water volume and annual amounts of N, Ca and Mg were reduced, while K, P and S 1 were increased in stemflow after removing epiphytes on boles and branches.Plot- and catchment level approaches were applied to determine nutrient output from the ecosystem during the study period. The results indicated that this catchment has a subsurface flow system. The amounts of percolation water varied with soil depths. Concentrations of all nutrient elements studied were greater in surface water than in soil solution and stream water. The budgets for all nutrient elements between atmospheric inputs and outputs by both seepage and stream flow were positive, except for calcium (negative).This forest appears to be characterized by relatively high nutrient return (5.6-8.0 % of the total storage) and low nutrient retention (2.0-2.7 % of the total storage). The relative rate of nutrient cycling occupies an intermediate position between temperate evergreen broad-leaved forest and tropical montane rain forest, it is closer to montane rain forests in rates of nutrient circulation.